ANALISIS TEKSTUAL DAN KONTEKSTUAL DALAM BAHAN BACAAN LITERASI BAHASA JAWA SD KELAS 4 DI KABUPATEN MADIUN - Nur Samsiyah; Winda Ayu Cahya (Universitas Negeri Surabaya, 2018)
Literacy reading is still rarely done is the Java language literacy. One of the factors that caused the lack of Java language literacy among them, is still rarely encountered reading Javanese language. This study aims to analyze textually and contextually the reading material of Java language class IV literature. This research is a qualitative research. this research data is obtained from the reading of Java language literacy in Madiun district. Based on the result of the research, there are data of grammatical and lexical and contextual aspects contained in the reading of Java class IV language literacy in Madiun district.